2004
DOI: 10.1161/01.res.0000131497.73744.1a
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Dependent Dilation Mediated by Endogenous Kinins Requires Angiotensin AT 2 Receptors

Abstract: Abstract-The vascular kallikrein-kinin system contributes to about one third of flow-dependent dilation in mice carotid arteries, by activating bradykinin B 2 receptors coupled to endothelial nitric oxide (NO) release. Because the bradykinin/NO pathway may mediate some of the effects of angiotensin II AT 2 receptors, we examined the possible contribution of AT 2 receptors to the kinin-dependent response to flow. Changes in outer diameter after increases in flow rate were evaluated in perfused arteries from wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 48 publications
4
52
0
Order By: Relevance
“…15,39 In addition, in Mas-deficient mice, the specific binding of Ang-(1-7) to kidney slices was abolished, whereas the binding of Ang II to AT 2 receptors was fully preserved. 15 Thus, a functional interaction such as a cross-talk mechanism or a permissive role for the AT 2 receptor for some Masmediated effects, as recently suggested for B 2 receptormediated bradykinin effects, 45 should be considered. It should be pointed out that, despite its putative interaction with the Ang-(1-7) receptor Mas, the role of AT 2 receptors within the RAS is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…15,39 In addition, in Mas-deficient mice, the specific binding of Ang-(1-7) to kidney slices was abolished, whereas the binding of Ang II to AT 2 receptors was fully preserved. 15 Thus, a functional interaction such as a cross-talk mechanism or a permissive role for the AT 2 receptor for some Masmediated effects, as recently suggested for B 2 receptormediated bradykinin effects, 45 should be considered. It should be pointed out that, despite its putative interaction with the Ang-(1-7) receptor Mas, the role of AT 2 receptors within the RAS is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Since in vitro flow-dependent dilation is known to be partially NO dependent (22)(23)(24) and Cav-1 is considered a negative regulator of eNOS function (2,3,25), we examined responses to another endothelium-dependent vasodilator, acetylcholine (Ach), in pressurized carotid arteries. In carotid arteries isolated from eNOS knockout mice, Ach-mediated vasodilation is absent, demonstrating that eNOS-derived NO is the major endothelial-derived relaxant in these vessels (26).…”
Section: Generation Of Transgenic Mice Expressing Endothelialmentioning
confidence: 99%
“…It is well established that there are interactions between bradykinin and Ang-(1-7), as well as other components of the RAS that may reflect an interaction through the common metabolism pathway involving angiotensin-converting enzyme, release of bradykinin by Ang-(1-7), or potential receptor interactions. [2][3][4][5] In an earlier study, however, we demonstrated that the effects of a peptidic angiotensin-converting enzyme inhibitor injected acutely into the nucleus of the solitary tract were mediated primarily by Ang-(1-7) but not by bradykinin. 6 Specifically, the selective Ang-(1-7) antagonist d-Ala 7 -Ang-(1-7) (A779) blocked the improvement in the baroreflex, but the bradykinin antagonist HOE 140 had no effect in that study.…”
mentioning
confidence: 70%